The phycosphere and its role in algal biofuel production - Yarbro, Jake; Khorunzhy, Emma; Boyle, Nanette (Frontiers in Climate, 2024)
Oleaginous microalgae have become a focus for large-scale biofuel production due to their ability to accumulate large quantities of lipids [1]. However, production is currently limited by cost and predation [2]. At present, algal biofuel cultivation is optimized through starvation, supplementing media with nutrients, or genetic engineering; these methods can often be costly with little to no increase in lipid production or the culture's defense. Investigating the phycosphere of algal-bacterial interactions may overcome these current barriers to large-scale production. The phycosphere of algalbacterial interactions have formed over millions of years through mutualistic and symbiotic relationships and can provide a more direct source of nutrients compared to adding the nutrients in bulk [3]. The most promising of these interactions include the production of phytohormones and quorum signaling compounds that alter the behaviors of the consortia. Phytohormones can improve algal growth rates, lipid production, and stress resistance. Quorum signaling could create consortia capable of warding off invaders-such as rotifers-while self-regulating and altering behavior based on population density [4]. Mechanisms within the algal phycosphere present many opportunities for the development of novel engineering strategies to further improve algal lipid production and operational costs. This review outlines previous preliminary phycosphere research as well as posing possible opportunities to be pursued in future biofuel production.